Implementing network-RTK: the SydNET CORS infrastructure - Rizos, Chris; Yan, Thomas; Omar, Samir; Musa, Tajul A; Kinlyside, D (Menay Pty Ltd, PO Box 1237, MILTON, QLD 4064 AUSTRALIA, 2003)
As is well known, the limitation of single-base real-time kinematic (RTK) GPS carrier phase-based techniques is the constrained distance between base receiver and the rover receiver due to distance-dependent measurement biases. For high productivity GPS surveying techniques, requiring very fast on-the-fly ambiguity resolution, the baseline length is generally restricted to less than 10km. However, techniques have been developed to overcome this distance dependence using a network of GPS reference stations. Because the measurement biases can be modelled and corrected for using multi-reference receiver data, the positioning accuracy will be almost independent of the inter-receiver distance. This class of techniques is now variously referred to as Network-RTK, Multi-Reference Station Positioning, Wide Area Positioning, and the Virtual Reference Station Technique. The authors will describe the basis of Network-RTK techniques, and discuss the challenges in implementing the infrastructure necessary to support Network-RTK users in Sydney. This paper will also describe the components of a continuously operating reference station (CORS) network currently being established in the Sydney basin area, suitable for supporting Network-RTK techniques.